Extended safety and tolerability of subcutaneous CAP256V2LS and VRC07-523LS in HIV-negative women: study protocol for the randomised, placebo-controlled double-blinded, phase 2 CAPRISA 012C trial - (:unkn) unknown (My University, 2023)
Introduction Women-controlled HIV prevention technologies that overcome adherence challenges of available daily oral pre-exposure prophylaxis and give women a choice of options are urgently needed. Broadly neutralising monoclonal antibodies (bnAbs) administered passively may offer a valuable non-antiretroviral biological intervention for HIV prevention. Animal and human studies have demonstrated that bnAbs which neutralise HIV can prevent infection. The optimal plasma antibody concentrations to confer protection against HIV infection in humans is under intense study. The Centre for the AIDS Programme of Research in South Africa (CAPRISA) 012C trial will evaluate extended safety and pharmacokinetics of CAP256V2LS and VRC07-523LS among young HIV-negative South African and Zambian women. The study design also allows for an evaluation of a signal of HIV prevention efficacy. Methods and analysis CAPRISA 012 is a series of trials with three distinct protocols. The completed CAPRISA 012A and 012B phase 1 trials provided critical data for the CAPRISA 012C trial, which is divided into parts A and B. In part A, 90 participants were randomised to receive both CAP256V2LS and VRC07-523LS at 20 mg/kg or placebo, subcutaneously every 16 or 24 weeks. Part B will enrol 900 participants in South Africa and Zambia who will be randomised in a 1:1 ratio and receive an initial loading dose of 1.2 g of CAP256V2LS and VRC07-523LS or placebo followed by 600 mg of CAP256V2LS and 1.2 g of VRC07-523LS or placebo subcutaneously every 6 months. Safety will be assessed by frequency and severity of reactogenicity and other related adverse events. Pharmacokinetics of both antibodies will be measured in systemic and mucosal compartments over time, while participants will be monitored for breakthrough HIV infections. Ethics and dissemination of study findings The University of KwaZulu-Natal Biomedical Research Ethics Committee and South African Health Products Regulatory Authori
Keywords: African Research